Understanding neuromuscular responses to pharmacological and exercise interventions: Manipulating motor unit plasticity in humans to improve muscle function - Jones, Eleanor J. (2024)
Sarcopenia, the loss of muscle mass and strength observed with ageing, presents a challenge to the growing ageing population and healthcare services. Motor unit (MU) numbers decrease with age but have remodelling potential, with the ability to rescue denervated fibres via axonal sprouting and reinnervation. Exercise interventions targeting the ageing musculoskeletal system, particularly resistance exercise training (RET), have showed promise in ameliorating declining function, however, blunted hypertrophic responses in the muscles of the older population demonstrate the need for further investigation of the neuromuscular system to develop optimal interventions.